New fossil booklice from the Cretaceous amber of Myanmar (Psocodea: Troctomorpha: Amphientometae: Manicapsocidae). (February 2017) - Azar, Dany; Hakim, Marina; Huang, Diying; Cai, Chenyang; Nel, André
Abstract: Palaeomanicapsocus margoae gen. et sp. nov. and Palaeomanicapsocus fouadi gen. et sp. nov. are characterized, described, illustrated, from the Cretaceous Burmese amber. Their phylogenetic position is discussed. These fossil taxa are the first manicapsocid barklice to be described from the Burmese amber.